2019
DOI: 10.3390/su11133572
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Spatial Pattern Analysis on Dengue Cases in Seremban District, Negeri Sembilan, Malaysia

Abstract: Dengue fever disease increases alongside urbanization rate in tropical countries. Hence, the need to visualize the distribution pattern of increases is vital for the management of dengue cases, especially in Malaysia. Thus, the dengue surveillance system is proposed for the monitoring of dengue cases using computer-generated modeling for spatial distribution patterns, which is important for management and control. The present study performed distribution and spatial pattern analysis of dengue cases reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
0
22
0
2
Order By: Relevance
“…Estos datos demuestran que el comportamiento del dengue a lo largo de los años es dinámico y que a pesar de los constantes esfuerzos por controlar el vector y mitigar la transmisión del virus existen ciertos patrones de los brotes que coinciden con los que se presentan a nivel regional e inclusive mundial, 19,20 es decir, la distribución geográfica puede ser el resultado de características climáticas como la temperatura y la humedad con modificaciones en el ámbito ecológico, que han contribuido a la expansión de los vectores Aedes aegypti y A. albopictus. Por otro lado, factores demográficos como el aumento en la densidad de la población, migración humana y turismo favorecen también a la transmisión de casos de dengue.…”
Section: Discussionunclassified
“…Estos datos demuestran que el comportamiento del dengue a lo largo de los años es dinámico y que a pesar de los constantes esfuerzos por controlar el vector y mitigar la transmisión del virus existen ciertos patrones de los brotes que coinciden con los que se presentan a nivel regional e inclusive mundial, 19,20 es decir, la distribución geográfica puede ser el resultado de características climáticas como la temperatura y la humedad con modificaciones en el ámbito ecológico, que han contribuido a la expansión de los vectores Aedes aegypti y A. albopictus. Por otro lado, factores demográficos como el aumento en la densidad de la población, migración humana y turismo favorecen también a la transmisión de casos de dengue.…”
Section: Discussionunclassified
“…Further increase in dengue cases will impede the growth of Bandar Baru Bangi urbanization in the future. This is because of the higher the rate of dengue infection, the lower the livability of the area [24]. Thus new methods for controlling dengue fever targeted at frequent hotpot locality are increasingly needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the main dengue vectors are active via Aedes mosquitoes when the temperature in the surrounding area is below 28°C. Aedes mosquitoes also need clean stagnant water to reproduce and lay eggs [24]. Female Aedes aegypti lay eggs usually on the interior walls of arti cial containers.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the ellipse is elongated features and have a particular orientation. Disease surveillance studies used ellipses to model spatial distribution since the central tendency and dispersion are two principal aspects, particularly to epidemiologists [32]. ArcGIS10.5 software used to conduct these spatial statistical analyses.…”
Section: Standard Deviational Ellipse (Sde)mentioning
confidence: 99%